Model Integrasi Ilmu Pengetahuan dan Agama Antara Dikotomi Naif dan Valid - Abu Amar (PUSAT PENELITIAN DAN PENGABDIAN MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2021)
The purpose of writing this article is to determine the concept of integrating science with Islamic studies and to unravel the dichotomous, naive and valid or dialogical scientific integration model. The approach used in the discussion starts from deciphering the concept of understanding and types of knowledge, classification of science in the Islamic perspective and discussion of the perspective and model of integration of science and religion, especially in Islamic higher education institutions. The writing of this article is based on the application of the comparative method of science integration concepts, especially according to classical Muslim scientists and contemporary Muslim scientists. Data obtained from various writings on the topic of scientific integration in Islamic higher education. The conclusion is obtained from the application of content analysis or content analysis. The problem of integration between science and religion can basically be mapped into three models, namely the dichotomous, naive, and valid or dialogical integration model. In reality, the problem of scientific integration is a problem faced by the world of Islamic education. This problem is due to the ambiguity of the meaning of the science concept on which it is based. So to reduce the negative impact of scientific integration is to return the meaning of science to its generic